(untitled) (Вестник КазНУ. Серия Экономическая, 2016)
Comprehensive assessment of the effectiveness of regional governance should be multilateral and present a system of indicators characterizing the regional administration in various aspects. The method of evaluating the effectiveness of strategic management was used in this article, which is for evaluation of socioeconomic development of regions by the methodology of Piven I.G. The method allows evaluating the effectiveness of the strategic regional management through the indicating of separate groups of the balanced scorecard based on the calculation of integrated indicators using the correction coefficients for each group.